INTERPRETASI FAMILY VALUES PADA FILM KELUARGA CEMARA - Renata Winahyu, Maria; Sunarto, Sunarto; Bayu Widagdo, Muhammad (Interaksi Online, 2024)
Film is one of the media used to spread information or messages to the public. Filmmakers have a vision and mission in making a film, not just for entertainment, but also to convey values that reflect social conditions and critique various aspects of life. "Keluarga Cemara" is a film released in 2019 that focuses on Abah's efforts to keep his family together with Emak, Euis, and Ara after facing bankruptcy. This study aims to identify the family values presented in the film's scenes by understanding the filmmaker's intentions in creating "Keluarga Cemara." This research uses a qualitative study by Schleiermacher's hermeneutic analysis method, which interprets a text by analyzing two parts: the cortex and the nucleus. The cortex analysis involves grammatical and semantic analysis by considering the context of the object, while the nucleus contains textual interpretation by the filmmaker, considering norms, values, and ideologies. The theories used in this study are organizational control theory and representation theory. The results of the study show that the filmmaker of "Keluarga Cemara" pays attention to social issues related to family by portraying family values into the film. Out of the 71 scenes in the film, 17 selected scenes highlight family values such as togetherness, stability, and loyalty. This film reflects social phenomena happening in society, especially family-related issues. In this regard, film industry professionals are expected to play a dominant role in being more selective in choosing the narratives or themes presented in films.